OSU-T315 as an Interesting Lead Molecule for Novel B Cell-Specific Therapeutics - Kristien Van Belle; Jean Herman; Mark Waer; Ben Sprangers; Thierry Louat (Journal of Immunology Research)
B cells are pathogenic in various disease processes and therefore represent an interesting target for the development of novel immunosuppressants. In the search for new therapeutic molecules, we utilized an in vitro B cell activation assay with ODN2006-stimulated Namalwa cells to screen a chemical library of small molecules for B cell modulating effects. OSU-T315, described as an inhibitor of integrin-linked kinase (ILK), was hereby identified as a hit. On human and murine primary B cells, OSU-T315 potently suppressed the proliferation and the production of antibodies and cytokines upon stimulation, suggesting that ILK could be a promising target in the modulation of B cell activity. Mice with B cell-specific knockout of ILK were generated. Surprisingly, knockout of ILK in murine B cells did not affect B cell function as assessed by several in vivo and ex vivo B cell assays and did not alter the B cell immunosuppressive activity of OSU-T315. In conclusion, OSU-T315 displays potency as B cell modulator, probably through a mechanism of action independent of ILK, and might serve as lead drug molecule for the development of novel B cell-selective drugs.